PENYELENGGARAAN MIGRASI RETENSI DATA REKAM MEDIS ELEKTRONIK RSUD NGUDI WALUYO WLINGI BLITAR: Implementation of Electronic Medical Records Data Retention Migration at Ngudi Waluyo Wlingi Blitar Regional Hospital - Ansyori, Anis; Pamungkas, Dihanung Wahyu; Maulid, Maylani Annisa (ASSYIFA : Jurnal Ilmu Kesehatan, 2024)
In the era of digitalization, hospitals in Indonesia face challenges in migrating electronic medical record data from the old system to the new system. At Ngudi Waluyo Wlingi Blitar Regional Hospital, an efficient and effective electronic medical record data migration process is the main issue that needs to be addressed to ensure the successful implementation of the Looker Studio web-based system. This research uses descriptive quantitative methods. This research shows that although the process of migrating electronic medical record data at Ngudi Waluyo Wlingi Blitar Regional Hospital is generally successful, there are several technical and training obstacles that must be corrected. This research aims to identify the challenges faced, the effectiveness of the procedures implemented, and the impact of implementing an electronic medical record system on the efficiency and accuracy of medical data storage. Recommendations for improvement include increasing training for officers, strengthening IT infrastructure, and more detailed planning for future data migration stages.